2017
DOI: 10.1002/macp.201700128
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Aqueous Heterogeneous Radical Polymerization of Styrene under Compressed CO2

Abstract: Radical polymerization of styrene in aqueous emulsions pressurized by CO2 has been investigated with a view to development of low energy miniemulsion polymerization. The general requirement of high energy mixing to generate miniemulsions comprising sub‐micrometer‐size monomer droplets has long been an impediment to wide‐spread industrial application. It is demonstrated by use of online dynamic light scattering and visual observation that CO2 pressurization to the so‐called transparency pressure of an emulsion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Environmentally friendly CO 2 has attracted significant interest over the years as a polymerization medium (supercritical CO 2 in dispersion/precipitation polymerizations) as well as a convenient means of generating miniemulsions . We have previously reported that CO 2 can be used to tune the particle morphology in dispersion PISA of styrene using a 4‐vinylpyridine macroRAFT agent in isopropanol and ethanol/water .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmentally friendly CO 2 has attracted significant interest over the years as a polymerization medium (supercritical CO 2 in dispersion/precipitation polymerizations) as well as a convenient means of generating miniemulsions . We have previously reported that CO 2 can be used to tune the particle morphology in dispersion PISA of styrene using a 4‐vinylpyridine macroRAFT agent in isopropanol and ethanol/water .…”
Section: Methodsmentioning
confidence: 99%
“…[18,21,32,33] Environmentally friendly CO 2 has attracted significant interest over the years as a polymerization medium (supercritical CO 2 in dispersion/precipitation polymerizations) [34][35][36] as well as a convenient means of generating miniemulsions. [37][38][39] We have previously reported that CO 2 can be used to tune the particle morphology in dispersion PISA of styrene using a 4-vinylpyridine macroRAFT agent in isopropanol and ethanol/ water. [40] In the presence of CO 2 (8 MPa), the morphologies shifted toward structures of higher interfacial core/corona curvature (i.e., a shift from vesicles to worms to spheres) relative to the case without CO 2 .We have recently reported a convenient strategy for modulating the coronal charge density in aqueous dispersion PISA of 2-hydroxypropyl methacrylate (HPMA) using a statistical copolymer of N,N-diethylaminoethyl methacrylate (DEAEMA) and poly(ethylene glycol) methyl ether methacrylate (PEGMA, M n = 475 g mol −1 ) as the stabilizer block.…”
mentioning
confidence: 99%
“…Indeed, although the same amount of surfactant has been used for all experiments, the smallest nanoparticles are obtained when the reaction was conducted at P t (Δ P t =0, Table , entries 3, 5, and 8), whereas larger nanoparticles were observed if the pressure was above or below P t (Figure A). As detailed in our previous publications, it is proposed that the smallest particle size is obtained at P t as a result of (i) matching RIs leading to minimization of attractive van der Waals forces between droplets, and (ii) expansion of the dispersed phase with CO 2 causing a reduction in droplet viscosity, which in turn facilitates mechanically induced (stirring) fission of droplets. Based on the presumed miniemulsion‐type mechanism, the number of droplets/particles would ideally remain constant throughout the polymerization.…”
Section: Figurementioning
confidence: 98%
“…Inspired by the pioneering work of Zhang et al, it has been recently reported that applying CO 2 pressure to an oil‐in‐water emulsion can be an efficient and simple means of controlling the droplet size in a miniemulsion . Miniemulsion generation (i.e.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation